Emergency Medicine Standardized Letter of Evaluation (SLOE): Findings From the New Electronic SLOE Format - Jackson, Jennifer S. (J Grad Med Educ, 2019)
BACKGROUND: Emergency medicine (EM) uses a standardized template for residency application letters of recommendations. In 1997, the Standardized Letter of Recommendation was developed with categories for applicant comparison. Now named the Standardized Letter of Evaluation (SLOE), it is a universal requirement in the EM residency application process. In 2016, a website called “eSLOE” was launched for credentialed academic EM faculty to enter applicant data, which generates a SLOE. OBJECTIVE: This article outlines website creation for the eSLOE and its successful national implementation in the 2016–2017 EM residency application cycle. We analyzed current trends in applicant assessments from the eSLOE data and compared them to prior data. METHODS: Data from 2016–2017 were sorted and analyzed for each question on the eSLOE. An analysis of Global Assessment and Qualifications for EM rankings, clerkship grade, and comparison with prior SLOE data was performed. RESULTS: Analysis of 6715 eSLOEs for 3138 unique applicants revealed the following Global Assessment rankings: top 10%, top one-third, middle one-third, and lower one-third. There was less spread with the distribution for clerkship grade and Qualifications for EM. The 2011–2012 standard letter of recommendation global assessment data, with top 10%, top one-third, middle one-third, and lower one-third, also revealed top-clustered results with less spread compared with the ranking usage in 2016–2017. CONCLUSIONS: Results indicate an improved spread of all rank categories for Global Assessment, enhancing the eSLOE's applicant discrimination. There has been an overall improvement in rank designation when compared with previously published data.